Alloying the surface of AISI 2205 duplex stainless steel material by PTA welding method and making its thermomechanical investigation in ANSYS software - Dikbas, Halil; Taskaya, Semih (Springer, 2020)
AISI 2205 steel is a duplex stainless steel plate containing 22% Cr, 3% Mo and 5-6% Ni and having the properties like high strength, impact toughness and corrosion resistance. In plasma transfer arc (PTA) welding method, the arc occurs between the tungsten electrode and the workpiece. In this study, the surface of AISI 2205 steel material was alloyed by PTA welding method using different combinations of TiC and B4C powders. The effect of B4C and TiC powders on AISI 2205 steel in coating process performed by PTA welding was investigated. The coating layer was investigated with the help of microhardness, optic microscope, SEM and XRD. As a result of optical microscope, microstructure examinations and microhardness values, it was determined that the coating layer and substrate were bonded to each other metallurgically, there was a significant increase in the hardness values in the presence of B4C and also metal carbide (MC) and metal boride (Me-B) phases formed in the structure. The highest increase in hardness was observed in the sample N4. TiC mixture decreased when B4C rate was 75% increased and the hardness values in the coating region by 330-457 HV. Finally, in the thermomechanical analysis results we found that axes-dependent thermal and residual stresses of the alloying layer increased along the welding. It is clear that the stress distribution along the weld line was the same. At both ends of the weld, there was only a small reduction in the stress size. It was determined that the highest stress concentration existed in the highest cross-sectional area.
2nd International Conference on Physical Chemistry and Functional Materials (PCFM) -- JUN 25-27, 2019 -- Cappadocia, TURKEY
Keywords: AISI 2205; Alloy; Plasma transfer arc welding; ANSYS; Thermomechanical